Resistensi Antibiotik pada Escherichia coli yang Diisolasi dari Daging Ayam pada Pasar Tradisional di Kota Bogor (ANTIBIOTIC RESISTANCE IN ESCHERICHIA COLI ISOLATED FROM CHICKEN MEAT OF TRADITIONAL MARKETS IN THE CITY OF BOGOR) - Januari, Connie; Sudarwanto, Mirnawati Bachrum; Purnawarman, Trioso (Jurnal Veteriner; Vol 20 No 1 (2019)DO - 10.19087/jveteriner.2019.20.1.125, 2019)
Antibiotic use in farm is spread widely to treat of poultry disease including therapy, supportive or preventive use and as afeed additive to improve chicken performance. The negative effects of antibiotic use can increase the level of bacterial resistance to antibiotics. This study aimed to investigate on antibiotic resistance in Escherichia coli isolated from chicken meat that were sold in Traditional Market of Bogor City. A total of 175 samples of chicken meat were taken by purposive sampling method, out of 175 found 50 positive samples of E. coli. The samples were subjected to E. coli examination and the isolated E. coli were tested for the antibiotic resistance using eight antibiotics, i.e., amoxicillin, cefotaxime, colistin, nalidixid acid, streptomycin, erythromycin, oxytetracillin, and tetracycline. The study was conducted by using the disk diffusion method on Muller-Hinton agar according to the Clinical and Laboratory Standards Institute guidelines. The study showed E. coli isolated from chicken meat were resistance towards amoxicilin (90%), colistin (94%), nalidixid acid (86%), streptomycin (98%), erythromycin (98%), oxytetracillin (84%), tetracycline (86%), and cefotaxime antibiotics (12%). The proportion of multidrugresistant was 99%. The higher of multidrug-resistant indicated the E. coli would be a threat to public and environmental health.